What have We Learned from “Perturbing” the Human Cortical Motor System with Transcranial Magnetic Stimulation? - Chouinard, Philippe A.; Paus, Tomáš (Frontiers in Human Neuroscience, 2010)
The purpose of this paper is two-fold. First, we will review different approaches that one can use with transcranial magnetic stimulation (TMS) to study both its effects on motor behavior and on neural connections in the human brain. Second, we will present evidence obtained in TMS-based studies showing that the dorsal premotor area, the ventral premotor area, the supplementary motor area, and the pre-supplementary motor area each have different roles to play in motor behavior. We highlight the importance of the dorsal premotor area in response selection based on arbitrary cues and in the control of arm movements, the ventral premotor area in grasping and in the discrimination of bodily actions, the supplementary motor area in movement sequencing and in bimanual coordination, and the pre-supplementary motor area in cognitive control. We will also discuss ways in which TMS can be used to chart ‘true’ cerebral reorganization in clinical populations and how TMS might be used as a therapeutic tool to facilitate motor recovery after stroke. We will end our review by discussing some of the methodological challenges and future directions for using this tool in basic and clinical neuroscience.